The incorporation and metabolism of amyloid-B into chylomicron-like lipid emulsions - James, Anthony; Pal, Sebely; Gennat, H.; Vine, Donna; Mamo, John (IOS Press, 2003)
The aggregation and deposition of amyloid-g (Ag) in the brain is thought to be an early event in the pathology of Alzheimer's disease (AD). Many studies have reported the association of Agwith lipoproteins from plasma suggesting an involvement of lipoprotein particles in Ag transport. Chylomicron-like lipid emulsions, resembling chylomicrons in composition, size and metabolism were prepared in the presence of [^{125}I]Ag1-40. Ag was found to associate significantly with these lipid emulsions during their preparation. The chylomicron-like emulsions containing Ag were then injected into a lateral ear vein of conscious rabbits and blood sampled at regular intervals up to 30 mins. It was observed that there was no difference in the plasma clearance of [^{125}I]Ag and that of the ^3H-cholesteryl ester, a marker of the emulsion particles, demonstrating that Ag remains associated with these particles throughout both their lipolysis and tissue uptake. Our results show thatg can be metabolised in association with triglyceride rich lipoproteins (TRLs). In addition we report the presence of specific markers of TRLs of hepatic and intestinal origin in human CSF thus suggesting a potential means of cerebral Ag delivery.